Infrared Spectroscopic Evidence of WS2 Morphology Change With Citric Acid Addition and Sulfidation Temperature - Zavala-Sanchez, Luz A.; Maugé, Françoise; Portier, Xavier; Oliviero, Laetitia (Frontiers in Chemical Engineering, 2022)
MS2 morphology is strongly influenced by several parameters including the addition of a chelating agent and sulfidation temperature. In this work, citric acid was used as chelating agent to prepare a series of WS2/Al2O3 catalysts that were sulfided at several temperatures. The effect of these two parameters in the morphology of the slabs was explored by means of low temperature CO adsorption followed by IR spectroscopy (IR/CO) and High-Resolution Scanning Transmission Electron Microscopy equipped with High Angular Annular Dark Field detector (HR STEM- HAADF). This allowed to depict the morphology of WS2 slabs by means of calculating the M-edge/S-edge site ratio. Addition of citric acid promotes the increase of S-edge site concentration whereas it keeps that of M-edge sites: according to IR/CO the morphology of WS2 is thus progressively modified from a slightly truncated triangle with predominately M-edge to a hexagon with both M-edge and S-edge with increasing citric acid amount. In addition, HR STEM-HAADF, demonstrated that the addition of citric acid in the preparation of W catalysts significantly reduces the size of WS2 nano-slabs increasing their dispersion degree. It is found that the morphology of WS2 slabs on WS2/Al2O3 catalyst under typical sulfidation temperature range (573 to 673 K) is a truncated triangle exposing both the M-edge and S-edge. Furthermore, the IR/CO data indicate that the degree of truncation (ratio of S-edge/M-edge) of WS2 slabs gradually increases with increasing sulfidation temperature. However, the most determining factor for a modification of the morphology of the slabs turns out to be the presence of citric acid as a chelating agent and not the sulfidation temperature. This morphology change is of great importance for catalytic performance, since the M-edge and the S-edge show different reactivity in hydrodesulfurization (HDS) reactions. As a further step, it was also found that the addition of citric acid not only improves the catalytic activity but also the stability of the catalysts, giving the best performance in concentrations higher than (CA / W = 1).